2015
DOI: 10.1021/acs.langmuir.5b00833
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Stability of MOF-5 in Humid Environments: Impact of Powder Densification, Humidity Level, and Exposure Time

Abstract: Metal-organic frameworks (MOFs) are an emerging class of microporous, crystalline materials with potential applications in the capture, storage, and separation of gases. Of the many known MOFs, MOF-5 has attracted considerable attention because of its ability to store gaseous fuels at low pressure with high densities. Nevertheless, MOF-5 and several other MOFs exhibit limited stability upon exposure to reactive species such as water. The present study quantifies the impact of humid air exposure on the properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 37 publications
9
71
0
Order By: Relevance
“…However, the absorption onset of MOF-5 appears at shorter wavelengths (310 nm). In fact, it has been reported that the exposure of MOF-5 to water 11 or moisture 11,13,[18][19] leads to distinctive products with well defined XRD patterns and reduced porosity, 13,20,21 which will be named in the following as MOF-5W and MOF-5H, respectively. Thus, these issues certainly need revision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the absorption onset of MOF-5 appears at shorter wavelengths (310 nm). In fact, it has been reported that the exposure of MOF-5 to water 11 or moisture 11,13,[18][19] leads to distinctive products with well defined XRD patterns and reduced porosity, 13,20,21 which will be named in the following as MOF-5W and MOF-5H, respectively. Thus, these issues certainly need revision.…”
Section: Introductionmentioning
confidence: 99%
“…This 55 nm blue shift in comparison with first reports is consistent with a ligand to ligand charge-transfer rather than a metal to ligand excitation mechanism, as commonly accepted 5,17 . The stability of MOF-5 under such conditions is a topic of renewed interest 20,21 . Another point of controversy originates from the use of MOF-5 as a photocatalyst in aqueous media 10 , considering its liability to hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…We find that the MOF-5 within our composite shows a similar scattering pattern to a form that has been degraded by humidity. 28 XRD patterns for the other composites (1%, 5%, 20%, 30%, and 50%) are found in the supporting information ( Figure S1) and also show incorporation of degraded MOF-5.…”
Section: Resultsmentioning
confidence: 95%
“…A previous study showed that MOF-5 degradation becomes measurable when exposed to 50% relative humidity for 24 hours. 28 In our protocols, the most likely step where humidity plays a role was the filtering process during the MOF-5 synthesis. A slurry of MOF-5 and chloroform (or DMF) was filtered through a 0.45-μm pore filter.…”
Section: Resultsmentioning
confidence: 99%
“…These "bare" metal sites interact strongly with many guest molecules, yielding higher binding energies and often resulting in denser arrangements of guests in the pores of the sorbent material. Unfortunately, the operative stability of bare metal-containing MOFs is often compromised by their ability to readily adsorb guests from the air, such as water and gaseous species, which can lead to permanent degradation of their crystallinity and adsorptive function [7][8][9]. By contrast, the excellent moisture stability of the well-known Zr6O4(OH)4(BDC)6 (where BDC = benzene-1,4-dicarboxylate, also known as UiO-66(Zr) material has been partially attributed to the absence of coordinatively unsaturated Zr in the Zr 6 O 4 (OH) 4 (CO 2 ) 12 oxide cluster, preventing hydrolytic attack by water molecules [8].…”
Section: Introductionmentioning
confidence: 99%